Planar Perovskite Solar Cells using CH3NH3PbI3 Films: A Simple Process Suitable for Large‐Scale Production. Issue 4 (17th February 2016) - Wang, Yangyang; Luo, Jiaming; Nie, Riming; Deng, Xianyu
Abstract: Despite the rapid progress of the power conversion efficiency (PCE) of perovskite solar cells, the reproducibility, stability, and large‐scale production are major challenges. Here, we present a simple and quick solution‐depositing process to achieve high‐quality perovskite films by adding an insulating polymer of polyacrylonitrile (PAN) as a film‐forming additive into the CH3 NH3 PbI3 solution. With the CH3 NH3 PbI3 :PAN films serving as an active layer, planar heterojunction perovskite solar cells show a PCE of 13.08 % at an area of 0.12 cm 2 and 7.32 % at a large area of 1.0 cm 2 . The PCE loss is only about 40 % from the small‐area to larger‐area devices fabricated by using a solution‐based deposition process. The measurements were performed in air without any device encapsulation. We also used the conjugated polymer poly(3‐hexylthiophene) (P3HT) as the alternative for PAN. The device performance indicates that the conjugated polymer is unsuitable as the additive, which we attribute to the photo‐induced charge transfer between CH3 NH3 PbI3 and P3HT. Abstract : Living large : An insulating polymer of polyacrylonitrile (PAN) is used as an additive for achieving high‐performance planar perovskite solar cells. The perovskite film is fabricated by one simple step of directly spin‐coating a CH3 NH3 PbI3 solution. The solar cells show a high power conversion efficiency (PCE) in both small and large areas, as measured in air without any device encapsulation.